Dampak Pernikahan Usia Muda Terhadap Sosial Ekonomi Keluarga - Annisa Zafa Safitri; Surdin; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
Early marriage can affect health, education, and psychology. Gunung Jati Village is one of the areas in Kendari City which is experiencing an increasing trend of early marriage. This study aimed to 1) find out the factors that cause young marriages in Gunung Jati Village, Kendari City; and 2) know the impact of young marriage on the socio-economic families in Gunung Jati Village, Kendari City. The method used in this research is descriptive qualitative. Data was obtained using observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion/verification. The results of the study show that: 1) the factors that cause young marriages in Gunung Jati Village, Kendari City are economic factors and married by accident; and 2) young marriage has an impact on the socio-economic families in the Gunung Jati Village, Kendari City, namely the difficulty of getting a steady job with a large income due to low education.